Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.

Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings - Domínguez Núñez, José Alfonso; Planelles González, Rosa; Rodríguez Barreal, José Antonio; Saiz de Omeñaca González, José Antonio (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.
Keywords: á mineral nutrition á; black truffle á drought; Black trufﬂe; Drought hardening; Elastic adjustment; elastic adjustment á inoculation; hardening á; Inoculation; Mineral nutrition; Nursery; nursery á osmotic adjustment; osmotic adjustment